How Emotions Shape Moral Behavior: Some Answers (and Questions) for the Field of Moral Psychology. Issue 1 (January 2015) - Teper, Rimma; Zhong, Chen‐Bo; Inzlicht, Michael
Abstract Within the past decade, the field of moral psychology has begun to disentangle the mechanics behind moral judgments, revealing the vital role that emotions play in driving these processes. However, given the well‐documented dissociation between attitudes and behaviors, we propose that an equally important issue is how emotions inform actual moral behavior – a question that has been relatively ignored up until recently. By providing a review of recent studies that have begun to explore how emotions drive actual moral behavior, we propose that emotions are instrumental in fueling real‐life moral actions. Because research examining the role of emotional processes on moral behavior is currently limited, we push for the use of behavioral measures in the field in the hopes of building a more complete theory of real‐life moral behavior.